Hyperphenylalaninaemia of various types among three-quarters of a million neonates tested in a screening programme. Issue 10 (October 1981) - Walker, V; Clayton, B E; Ersser, R S; Francis, D E; Lilly, P; Seakins, J W; Smith, I; Whiteman, P D
Abstract : A total of 795 382 infants born in north London was screened for phenylketonuria using the Guthrie test between October 1969 and December 1978. During this period it became recognised that phenylketonuria is not a single disease entity but one that encompasses a number of disorders of differing clinical and biochemical severity. The overall incidence of persistent hyperphenylalaninaemia was of the order of 7 per 100 000 births (or 1 in 15 000) and all the early treated patients made normal developmental progress. During the study there was an appreciable fall in the incidence of uncomplicated transient hyperphenylalaninaemia with or without tyrosinaemia. This reduction coincided with the change in infant feeding practice in the UK which led to lower intakes of protein and phenylalanine. It was concluded that any infant found to have a persistent blood phenylalanine concentration of 240 mumol/1 (4 mg/100 ml) or greater should be followed closely.